Regional utvecklingsplanering och grönstruktur - Palmstierna, Amanda (2006)
The aim of the thesis is to analyze the role of regional development planning concerning a regional perspective of green structure and to reflect on its future role. The target group of the study is foremost practitioners but also students of regional planning and development.